Studi Komparasi Aktivitas Antiradikal Bebas Ekstrak Metanol Kulit Buah Pisang Ambon (Musa acuminata Colla) Muda dan Matang dengan Metode DPPH - Abd. Malik; Reni Fauziah; Ahmad Najib (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Ambonese banana fruit peel has antioxidant, antimicrobial, and anti-inflammatory activities. This search aims to investigate the potential of free radical scavengers based on the binding of DPPH free radicals (1,1-Diphenyl-2-picryl Hidrazil). Ambonese banana fruit peel was extracted by maceration using methanol. Free radical activity assay on sample measured by inhibition of DPPH using spectrophotometer UV-Vis at a wavelength at 516 nm. Identification by the TLC method showed that the peel extract of Ambonese banana was active as free radical scavengers where the DPPH solution changed in color from purple to yellow after being sprayed. The calculation results in IC50 values of each sample methanol extract of unripe Ambonese banana fruit peel is 11.78 µg/mL, while the methanol extract of the ripe Ambonese banana fruit peel is 151.56 µg/mL. The standard quercetin has IC50 values of 4.44 µg/mL. The result showed that the methanol extract from the Ambonese banana fruit peel (Musa acuminata Colla) has antioxidantactivity.